Ghost dog secrets - Kehret, Peg (Puffin Books, 2011)
When a ghost collie leads sixth-grader Rusty to an injured dog that is chained outdoors in frigid weather, Rusty calls animal control then takes matters into his own hands aided by his best friend. Includes instructions for knitting cat blankets.